2018
DOI: 10.1136/jmedgenet-2017-105022
|View full text |Cite
|
Sign up to set email alerts
|

A false-carrier state for the c.579G>A mutation in the NCF1 gene in Ashkenazi Jews

Abstract: These results point to the existence of a 'false-carrier' state in Ashkenazi Jews and have wide implications regarding pre-pregnancy screening in this and other population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This assay simply quantitates GTGT and DGT sequences, regardless of whether these sequences are within their respective genes or within "fusion" genes that result from DNA recombination. 14,15 Despite the diversity of possible gene products, the ddPCR data are sufficient to segregate the patients, carriers, and kindred in most p47 phox CGD families. Advanced technologies such as multiplex ligation-dependent probe amplification are required to delineate the specific NCF1 defect.…”
Section: Genotyping With Ddpcrmentioning
confidence: 99%
“…This assay simply quantitates GTGT and DGT sequences, regardless of whether these sequences are within their respective genes or within "fusion" genes that result from DNA recombination. 14,15 Despite the diversity of possible gene products, the ddPCR data are sufficient to segregate the patients, carriers, and kindred in most p47 phox CGD families. Advanced technologies such as multiplex ligation-dependent probe amplification are required to delineate the specific NCF1 defect.…”
Section: Genotyping With Ddpcrmentioning
confidence: 99%
“…The variant is also frequent among Ashkenazi Jews although Ashkenazi chronic granulomatous disease patients with this variant have not been described [8, 9]. Carrier screening based on a uniform expanded pan Israeli preconception screening panel of an Ashkenazi couple while the woman was pregnant revealed that both spouses were heterozygotes the variant c.579G > A, and prenatal diagnosis was performed [15]. The fetus inherited both carrier alleles but was not affected; having substantial oxidase activity revealed by the analysis of fetal leucocytes obtained by cordocentesis.…”
Section: Population-specific Screening Program or Universal Screeningmentioning
confidence: 99%